Cold and hot region detectability and image quality enhancement in TC99m spect by reduction of scattered gamma photons prior to detectio - Sayed, Inayatullah Shah; Harun, Siti Zawani (2011)
Introduction: Single Photon Emission Computed Tomography (SPECT) inherits a serious problem of scattered gamma photons emanating from the object to be scanned. It is well recognised that, presence of scattered gamma photons in SPECT projection data, degrade the image quality and limit the accuracy in quantification of radioactivity distribution. Therefore, it is essential to remove the scattered gamma photons from SPECT projection data for better image quality and quantitative analysis. In this context, some techniques are available, which are window subtraction, mathematical (Monte Carlo simulation) and convolution technique. In this work a new technique has been introduced, that is a material filter technique, which absorbs some fraction of scattered gamma photons before they can reach to the surface of gamma camera detector.